2021
DOI: 10.2196/26125
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Attitudes Toward the Use of a Mobile Health App for Remote Monitoring of Gingivitis and Willingness to Pay for Mobile Health Apps (Part 3): Mixed Methods Study

Abstract: Background Gum infection, known as gingivitis, is a global issue. Gingivitis does not cause pain; however, if left untreated, it can worsen, leading to bad breath, bleeding gums, and even tooth loss, as the problem spreads to the underlying structures anchoring the teeth in the jaws. The asymptomatic nature of gingivitis leads people to postpone dental appointments until clinical signs are obvious or pain is evident. The COVID-19 pandemic has necessitated social distancing, which has caused many pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Patients who had a favourable attitude towards mobile health applications to manage DM were 5.20 times more likely to be willing to use mobile health applications (AOR 5.20; 95% CI 2.60 to 10.40). This finding is consistent with the findings of other studies 26 27. This demonstrates how patients’ attitudes towards mobile health technologies influence their willingness to use them positively.…”
Section: Discussionsupporting
confidence: 92%
“…Patients who had a favourable attitude towards mobile health applications to manage DM were 5.20 times more likely to be willing to use mobile health applications (AOR 5.20; 95% CI 2.60 to 10.40). This finding is consistent with the findings of other studies 26 27. This demonstrates how patients’ attitudes towards mobile health technologies influence their willingness to use them positively.…”
Section: Discussionsupporting
confidence: 92%
“…Another possible explanation is that individuals with higher education levels tend to have a higher level of health literacy, 25 which may facilitate their use of health apps and allow them to understand the benefits that health apps can offer. 26 We further infer from this finding that due to their intricacy, the use of certain health apps may be challenging for individuals with a lower level of educational attainment or health literacy. It is therefore crucial for developers to make health apps more accessible and user-friendly by prioritizing intuitive design in their health apps; this can be done by integrating concise instructions and optimizing the user interface design.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, the willingness of patients to pay for these services should also be considered. A study in this field concluded that patients are willing to pay if the mHealth technology is beneficial for them and improves their health [ 18 ].…”
Section: Discussionmentioning
confidence: 99%